A new synthetic method for non-symmetric pillar[5]arenes with simple isolation and improved yield. Issue 37 (11th September 2017) - Ding, Jiaming; Chen, Jiafu; Mao, Weipeng; Huang, Junrou; Ma, Da
Abstract : We developed a new synthetic method for non-symmetric pillar[ n ]arenes, which has improved yield and simple isolation. Abstract : The conventional method to synthesize non-symmetric pillar[ n ]arenes (PA[ n ]s) generally results in a low yield and requires laborious isolation. We developed a new synthetic method to prepare non-symmetric PA[5]s with various substitutions. Monomers were synthesized starting from commercially available chemicals. The desired products could be easily isolated with an improved yield.